Implikasi Hukum bagi Perseroan yang Mengabaikan Rapat Umum Pemegang Saham : Studi Kasus PT. Pitala Gunawan Raya - Adinda Ofi Salsabila Putri; Anandyta Putri Wardhana; Arvina Pradita Mufidatul Khusnah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
A Limited Liability Company (LLC) plays a pivotal role in the economic landscape, with the General Meeting of Shareholders (GMS) being one of its most vital organs. The GMS serves as a forum for making strategic decisions, overseeing company performance, and ensuring transparency and accountability. This study investigates the legal implications for companies, specifically PT. Pitala Gunawan Raya, that neglect to convene GMS as required by the Limited Liability Company Law. Using normative legal research with statute and case approaches, the study identifies gaps in the regulatory framework that need addressing to strengthen corporate governance and economic growth.